Comparación de cuatro protocolos analgésicos en caninos sometidos a ablación de cabeza de fémur en la clínica emergencias veterinarias de la ciudad de Cali (2021)
As we well know pain, it is all that unpleasant experience that every living being will be subjected to, whether of a tissue, emotional or potential type that leads to any type of discomfort, which in this case rules out that the inability of the living being by not being able to communicate or express your pain in a clear way, it does not mean that you are not suffering any discomfort with respect to the situation that is being subjected, that is why you should act immediately to an effective analgesia response through the Glasgow scale, the only and valid so far for the measurement of pain with its respective score that lead to a similar result with respect to what the patient is experiencing.